The End Of Reason - "Zacharias, Ravi K." ("Grand Rapids, Michigan :")
"Includes bibliographical references and index. Foreword -- Prologue -- The end of reason -- Notes -- Subject index. Taking on the challenge of the New Atheism head-on, Dr. Ravi Zacharias exposes the utter bankruptcy of the worldview of atheisms newest champion, author Sam Harris. Harris claims God is just an imaginary friend in his bestselling book, Letter to a Christian Nation. The End of Reason is a powerful and passionate reply not only to those who have read the writings of Harris, but to all Christians who have had the foundations of their beliefs decimated. This book dismantles the main arguments by Harris for atheism and answers his call to denounce Christian values. The author focuses on the goodness of God, the real nature of evil, and the foundation of true morality. - Publisher."
Keywords: APOLOGETICS.;CHRISTIANITY AND ATHEISM